Influence of a Polyherbal Mixture in Dairy Calves: Growth Performance and Gene Expression - Díaz Galván, Cesar; Méndez Olvera, Estela Teresita; Martínez Gómez, Daniel; Gloria Trujillo, Adrián; Hernández García, Pedro Abel; Espinosa Ayala, Enrique; Palacios Martínez, Monika; Lara Bueno, Alejandro; Mendoza Martínez, Germán David; Velázquez Cruz, Lucero Abigail (Frontiers in Veterinary Science, 2021)
A polyherbal feed mixture containing (Achyrantes aspera, Trachyspermum ammi, Citrullus colocynthis, Andrographis paniculata, and Azadirachta indica) was evaluated in growing calves through blood chemistry, blood biometry, and gene expression during the pre-ruminant to weaning period. Forty Holstein calves (initial BW 45.6 ± 3.2 kg; 22.8 ± 0.9 days post birth) from a dairy farm were randomly assigned to the following treatments: 0, 3, 4, and 5 g/d of a polyherbal mixture, dosed in colloid gels with gelatin. Calves were housed in individual outdoor boxes with ad libitum access to a 21.5% CP calf starter and water and fed individually with a mixture of milk and a non-medicated milk replacer (22% CP). Blood samples were collected on day 59 for blood chemistry, blood biometry, and gene expression analysis in leukocyte through microarray assays. Immunoglobulins were quantified by enzyme-linked immunosorbent assay. The animals treated with the polyherbal mixture showed a quadratic effect on final body weight, daily weight gain, final hip height, and final thoracic girth. The best performance results were obtained with a treatment dose of 4 g/d. The serum IgG increased linearly with the treatment doses. Gene set enrichment analysis of upregulated genes revealed that the three biological processes with higher fold change were tight junction, mucin type O-Glycan biosynthesis, and intestinal immune network for IgA production. Also, these upregulated genes influenced arachidonic acid metabolism, and pantothenate and CoA biosynthesis. Gene ontology enrichment analysis indicated that the pathways enriched were PELP1 estrogen receptor interacting protein pathways, nuclear receptors in lipid metabolism and toxicity, tight junction, ECM-receptor interaction, thyroid hormone signaling pathways, vascular smooth muscle contraction, ribosome function, glutamatergic synapse pathway, focal adhesion, Hippo, calcium, and MAPK signaling pathways.